(untitled) (Fiep Bulletin - online, 2013)
All military, due to their profession, should be able to handle stress, stand in action, persist in difficult circumstances and remain in combat. Good cognitive and affective capacities, joined with excellent physical fitness are predominant factors for their success in their actions. The aim of this research was to evaluate the levels of physical fitness through a training program before and after the assessment of soldiers who joined in 2006 and were part of the 33rd Motorized Infantry Battalion, in the city of Cascavel Parana. Semi-experimental study carried out with 81 soldiers, where the weight and height were evaluated, the Body Mass Index (BMI) was obtained through two evaluations and was correlated with the Physical Fitness Test (PFT) which is regulated by the Army General Staff, being these variables the 12 minute run, push-ups, sit-ups and pull-ups. For data analysis of the before and after assessment, a chi-square test with 5% of significance was used. The obtained results pointed out that in every carried-out test, the recruits showed statistically significant improvements. Regarding the 12-minute run, before and after assessment, 48% of the recruits improved their levels of physical fitness, 44% remained with the same levels and 7% reduced their performance. The pull-up variable showed that 65% of the recruits improved their performance in the last PFT related to the first one, 30% remained with the same levels while only 5% reduced their results. Therefore, it was concluded that the training program implemented for the recruits from the 33rd Motorized Infantry Battalion showed improvements compared to their physical fitness during the pre and post evaluation.